Serum adiponectin-levels are predictive of posttraumatic stress disorder in women - Eileen Vuong; Shibe Mhlongo; Esnat Chirwa; Carl Lombard; Nasheeta Peer; Sian Megan Hemmings; Naeemah Abrahams; Soraya Seedat (Neurobiology of Stress, 2022)
Background: Accumulative evidence indicates a role for adiponectin, a polypeptide secreted by adipose tissue, in the pathophysiology of posttraumatic disorder (PTSD) via metabolic and inflammatory pathways. This study examined adiponectin as a potential predictive biomarker for PTSD among female rape survivors. Methods: We evaluated the relationship of baseline serum adiponectin levels to the development of probable PTSD at 3- and 6-months post rape-exposure and compared adiponectin levels between 542 rape-exposed (RE) and 593 rape-unexposed women (RUE). Probable PTSD were defined as a Davidson Trauma Scale score ≥40. Data were analysed using multivariate regression models and a generalized estimating equation (GEE) model. We adjusted for clinically relevant covariates associated with PTSD, as well as adiposity indices. Results: Participants who were in the mid-and high adiponectin tertile groups versus the lowest tertile group had a significantly reduced risk of probable PTSD at 6 months follow-up, independent of adiposity(aOR = 0.45[0.22–1.05], p = 0.035; aOR = 0.44[0.22–0.90], p = 0.024). However, there was no effect of group (RE vs. RUE). Limitations: Adiponectin assays were conducted on non-fasting blood samples and information on chronic medication, dietary factors and levels of physical activity were not collected. There was a high attrition rate among rape exposed participants. Conclusions: Our results show that higher serum adiponectin levels are associated with reduced risk of probable PTSD over a 6-month period. This finding supports the hypothesis that serum adiponectin is a potential risk biomarker for PTSD.